Assessing and predicting Bojiang lake area and LULC changes from 2000 to 2045 - Muhammad Naeem; Yongqiang Zhang; Xiaoqiang Tian; Ping Miao; Congcong Li; Zhenwu Xu; Longhao Wang; Faisal Mumtaz; Zixuan Tang; Shaoyang He (Journal of Hydrology: Regional Studies)
Study region: This study focuses on the Bojiang Lake Basin in Erdos, China, covering an area of 744.56 km2. Study focus: While the global significance of lake ecosystems is well established, few studies have investigated the long-term dynamics of Bojiang Lake, particularly the interplay between human activities and climate change. This study assesses lake area fluctuations and land use/land cover changes in the Bojiang Lake Basin from 2000 to 2023 and provides projections for 2024–2045 using the CA-ANN model. New hydrological insights for the region: From 2000–2011, the lake’s surface area decreased by approximately 80 %, shrinking from 9.78 km2 to 1.92 km2. Between 2012 and 2023, the lake area recovered by 340 %, expanding to 8.49 km2, primarily due to increased precipitation and improved water management practices. Projections for 2024–2045 suggest further hydrological changes, with the lake area expected to increase by 42.67 %, reaching 12.17 km2 by 2045. Additionally, vegetation cover is expected to rise by 1.97 %, while barren land will decrease by 3.10 %. However, built-up areas are predicted to grow by 47.73 %, reflecting ongoing urban expansion. These findings emphasize the need for integrated land and water management strategies to balance urban growth with environmental conservation. Sustainable planning is crucial for mitigating the impacts of urbanization and climate change, ensuring the long-term ecological stability of the Bojiang Lake Basin.